2013
DOI: 10.1103/physrevx.3.011001
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Scattering from Metallic Nanostructures: Bridging the Gap between the Near-Field and Far-Field Responses

Abstract: We present here a detailed study of the complex relationship between the electromagnetic near-field and far-field responses of ''real'' nanostructured metallic surfaces. The near-field and far-field responses are specified in terms of (spectra of) the surface-enhanced Raman-scattering enhancement factor (SERS EF) and optical extinction, respectively. First, it is shown that gold nanorod-and nanotube-array substrates exhibit three distinct localized surface plasmon resonances (LSPRs): a longitudinal, a transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 41 publications
3
61
0
1
Order By: Relevance
“…Modern nanofabrication methodologies enable the creation of a number of different nanostructures with precisely controlled shapes, sizes, and spacing [3][4][5][6][7][8][9][10]. This has extended to the creation of a range of different metallic nanostructures array designs that produce localized surface plasmon resonances (LSPRs) [8][9][10][11][12][13][14][15]. One such design is based on arrays of quasi self-standing metal nanorods [13][14][15].…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Modern nanofabrication methodologies enable the creation of a number of different nanostructures with precisely controlled shapes, sizes, and spacing [3][4][5][6][7][8][9][10]. This has extended to the creation of a range of different metallic nanostructures array designs that produce localized surface plasmon resonances (LSPRs) [8][9][10][11][12][13][14][15]. One such design is based on arrays of quasi self-standing metal nanorods [13][14][15].…”
Section: Papermentioning
confidence: 99%
“…Quasi self-standing metallic nanorod arrays possessing a fixed nanorod diameter and interrod separation have been widely applied for SERS [12]. A limited number of studies have demonstrated that such nanomaterials can be applied to SEF [33].…”
Section: Papermentioning
confidence: 99%
“…Metallic nanostructures that possess anisotropic symmetry, such as nanorods, are reported to produce LSPRs with high quality factors. [16][17][18][19] Nanorod array design enables choice over precise particle shape, length, width and inter-particle coupling. Such nanorod arrays have been reported to support negative refraction at visible to near-infrared wavelengths or provide near-field focusing for sub-wavelength imaging.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 2D nanorod arrays have been applied to enable surface-enhanced Raman scattering (SERS) spectra from molecules adsorbed on the surface of vertically aligned gold nanorod arrays In addition, gold nanorods possess good chemical stability and biocompatibility under biological conditions. 17,21 Fluorescence spectroscopy is another well-known spectroscopic method playing a major role in selective detection of bioanalytes. 23 Similarly to the effect of increasing the Raman scattering of molecules, the presence of LSPRs on plasmonic metal nanostructures can enhance the fluorescence signal from locally situated fluorophores, a process known as metal enhanced (MEF) or surface enhanced fluorescence (SEF).…”
Section: Introductionmentioning
confidence: 99%
“…45 If the individual plasmonic nanostructures, pure metallic or metal-hybrid, come closer than the range (B30 nm) of the plasmonic E field, extremely intense local electromagnetic fields can be generated. 46 In contrast to the localized surface plasmons studied here, for pure metallic NWs, propagating surface plasmons with a guided character can also result in highsensitivity bio-sensing. 47 Furthermore, we are only using the classical electromagnetic theory for the calculation and interpretation of results; quantum mechanical effects or chemical enhancement effects have not been considered.…”
Section: For Experimental Verification Of the Fdtd Resultsmentioning
confidence: 99%